Climatic characteristics of the 2010-2016 drought in the semiarid Northeast Brazil region - JOSÉ A. MARENGO; LINCOLN M. ALVES; REGINA C.S ALVALA; ANA PAULA CUNHA; SHEILA BRITO; OSVALDO L.L. MORAES (Anais da Academia Brasileira de Ciências, 2017)
ABSTRACT This study discusses the climatological aspects of the most severe drought ever recorded in the semiarid region Northeast Brazil. Droughts are recurrent in the region and while El Nino has driven some of these events others are more dependent on the tropical North Atlantic sea surface temperature fields. The drought affecting this region during the last 5 years shows an intensity and impact not seen in several decades in the regional economy and society. The analysis of this event using drought indicators as well as meteorological fields shows that since the middle 1990s to 2016, 16 out of 25 years experienced rainfall below normal. This suggests that the recent drought may have in fact started in the middle-late 1990s, with the intense droughts of 1993 and 1998, and then the sequence of dry years (interrupted by relatively wet years in 2007, 2008, 2009 and 2011) after that may have affected the levels of reservoirs in the region, leading to a real water crisis that was magnified by the negative rainfall anomalies since 2010.